2021
DOI: 10.3389/fnhum.2021.755276
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing to Lose, Absolutely Everything to Gain”: Patient and Caregiver Expectations and Subjective Outcomes of Deep Brain Stimulation for Treatment-Resistant Depression

Abstract: Background: How “success” is defined in clinical trials of deep brain stimulation (DBS) for refractory psychiatric conditions has come into question. Standard quantitative psychopathology measures are unable to capture all changes experienced by patients and may not reflect subjective beliefs about the benefit derived. The decision to undergo DBS for treatment-resistant depression (TRD) is often made in the context of high desperation and hopelessness that can challenge the informed consent process. Partners a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Ethics approval was obtained from Monash University Human Research Ethics Committee (CF16/1888-2016000963) and all participants provided written informed consent. Separate data findings derived from these interviews on the topics of informed consent, participant expectations, and subjective patient outcomes are reported elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethics approval was obtained from Monash University Human Research Ethics Committee (CF16/1888-2016000963) and all participants provided written informed consent. Separate data findings derived from these interviews on the topics of informed consent, participant expectations, and subjective patient outcomes are reported elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unrealistic expectations can negatively impact satisfaction post-DBS and are correlated with poor psychosocial adjustment and functional outcomes (in Parkinson’s disease and epilepsy, no identified data in OCD) (Hasegawa et al, 2014; Maier et al, 2016). Furthermore, despite expressing realistic expectations, patients may hope for more (Thomson et al, 2021). Both family members and patients should not expect a cure, but be well informed of, and committed to, the post-operative regimen (as described below).…”
Section: Pre-operativementioning
confidence: 99%
“…Studies in major depressive disorder (MDD) have demonstrated that DBS patients generally report realistic expectations of outcomes, but they also (retrospectively) identified difficulties with attending to, processing and retaining the educational material presented as part of the consent process (Thomson et al, 2021). In our experience with OCD, compulsions can interrupt consenting discussions, and repeated questioning suggests poor retention.…”
Section: Pre-operativementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond altruism and a sense of purpose, the first of these subjects had hopes for a better life, "… there's so much I've suffered … I mean, I have not been able to work, I have not been able to do anything for 18 years." And with a sense of desperation, 57 "So it's more like might as well try it. I've lost everything" [P210].…”
Section: Reasons For Participatingmentioning
confidence: 99%